TAXPAYER COMPLIANCE: TAXPAYER BEHAVIOR ANALYSIS AND TAX AWARENESS AS A MEDIATING IN INDONESIA - Yulius Kurnia Susanto; Isabella Fiorita (Jurnal Bisnis dan Akuntansi, 2023)
The purpose of this research is to provide empirical evidence regarding the mediating effect of tax awareness on relation between tax knowledge and taxpayer compliance. The impact of the tax services, tax sanctions, tax payer environment, tax understanding, on taxpayer compliance. The sample used in this research are respondents who are taxpayers in DKI Jakarta, Indonesia and work as entrepreneurs or freelancers. The method used for sampling in this research is Convenience Sampling. The number of samples for this research is 63 respondents. Testing data using SEM-PLS. The results that were obtained from this research are tax awareness has medating influence on relation between tax knowledge and taxpayer compliance. Tax services and tax sanctions have an influence on taxpayer compliance. Meanwhile, for taxpayer environment and tax understanding have no effect on taxpayer compliance. A taxpayer who has tax knowledge is more likely to have tax awareness which ultimately obeys in paying and reporting taxes.